PENGARUH RESIDU BICOHAR TONGKOL JAGUNG DIPERKAYA AMONIUM SULFAT TERHADAP BEBERAPA SIFAT TANAH DAN PERTUMBUHAN TANAMAN JAGUNG MANIS DI pH TANAH YANG BERBEDA - Exclesia Ansila Sitohang; Wani Hadi Utomo (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Biochar is one of amandement soil that comes from imperfectly combustion (pyrolysis) form of natural charcoal. The addition of biochar as a soil reparing was able to increase the carbon in the soil that able to improve soil characteristic soil. The purpose of this study was to find out the influence of residual biochar enriched with amonium sulphate on soil chemical and physical properties, and plant growth on various soil acidity levels. Treatments tested for this study were biochar residues enriched by amonium sulfate, N fertilizer (BN), biochar residues (B), without biochar, N fertilizer (N), and control (K) and various degrees of soil pH, i.e. pH 6-7 (P1), pH 4-5 (P2), pH 5-6 (P3). Twelve treatments were arranged in a randomzed block design with three replicates. Variables observerd were properties of soils (pH, C-Organic, CEC, N-total, and aggregate stability), and maize growth parameters (plant height and the number of leaves). The results showed that aplication of biochar of residues maize cob enriched with amonium sulfphate and various pH soil had interactions towards soil CEC and soil N-total, and had an interactions towards plant growth at plant age of 8 weeks-10 weeks, and number of leaves at age 9 weeks-10 weeks.